Contrasting host use and feeding behavior by sympatric mesograzers - Paula, Caio A. [UNESP]; Borges, Dalila J. [UNESP]; Andrade, Aynara R. [UNESP]; Leite, Fosca P. P.; Costa, Tânia M. [UNESP]; Machado, Glauco B. O. [UNESP] (Wiley, 2023)
Marine mesograzers use macroalgae as food and habitat and may have strong top-down effects on plants and macroalgae. Sympatric mesograzer species often differ regarding host use and feeding behavior, which may lead to distinct impacts by these consumers on primary producers. The amphipods Hyale niger and Ampithoe marcuzzii are mesograzers abundant that co-occur in Brazilian waters and, although they use several macroalgae as habitat, it is unknown how much the food value of these hosts explains the host use pattern by the two mesograzers. Herein, we investigated the abundance and feeding behavior of the sympatric amphipods H. niger and A. marcuzzii. For that, their abundance on the macroalgal hosts Sargassum filipendula, Padina gymnospora, and Dichotomaria marginata was evaluated seasonally in a rocky shore at Fortaleza Beach, state of São Paulo, Brazil. Also, multiple-choice and no-choice feeding experiments were carried out at laboratory to evaluate the feeding behavior of these mesograzers. The abundance of H. niger was similar among the three macroalgal hosts (except during winter), while A. marcuzzii was more abundant on Dichotomaria and Padina than Sargassum in all seasons. Moreover, H. niger consumed more Padina than Dichotomaria and Sargassum in both feeding experiments. In turn, A. marcuzzii preferred to feed on Padina when it had a choice and consumed the three macroalgal hosts at similar levels in the no-choice feeding experiment. Overall, H. niger and A. marcuzzii differ from each other regarding their feeding behavior and host use pattern. In particular, the food value of macroalgae seems to partially explain the host use by A. marcuzzi, but not by H. niger. The differences between H. niger and A. marcuzzii may result in varying impacts on primary producers.
Keywords: amphipods; feeding choice; herbivore–plant interaction; macroalgae